The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.macromol.2c01742
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Escape of a Single Chain from a Diblock Copolymer Micelle

Abstract: We investigate the dependence of the free energy trajectory for chain expulsion from a diblock copolymer micelle in a selective solvent on core chain length through dissipative particle dynamics simulations and umbrella sampling. The free energy barrier scales linearly with the core block length of the expelled tracer chain for N core = 4−12, consistent with experiments. The simulations further reveal that the core chain undergoes a "hyperstretching" mechanism near the transition state, where the core block pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…According to Halperin and Alexander, the hydrophobicity of the core-forming block has a major influence on the exchange dynamics. This hydrophobicity can be tuned by modifying the B-block length , or by changing the chemistry of the hydrophobic block itself. , One versatile strategy is to incorporate hydrophilic units into the hydrophobic blocks. This was illustrated by Bendejacq et al and Billon et al who demonstrated that frozen block copolymers containing hydrophobic polystyrene B-blocks became dynamic when acrylic acid (AA) units were incorporated through copolymerization within the B-blocks.…”
Section: Introductionmentioning
confidence: 99%
“…According to Halperin and Alexander, the hydrophobicity of the core-forming block has a major influence on the exchange dynamics. This hydrophobicity can be tuned by modifying the B-block length , or by changing the chemistry of the hydrophobic block itself. , One versatile strategy is to incorporate hydrophilic units into the hydrophobic blocks. This was illustrated by Bendejacq et al and Billon et al who demonstrated that frozen block copolymers containing hydrophobic polystyrene B-blocks became dynamic when acrylic acid (AA) units were incorporated through copolymerization within the B-blocks.…”
Section: Introductionmentioning
confidence: 99%
“…More recent work has focused on the use of self-consistent field theory and coarse-grained molecular dynamics simulations of block polymer self-assembly and dynamics, including the origin of Frank−Kasper phases 5 and micellar chain exchange. 6 Finally, I want to give my sincere thank you to both Prof. Glenn Fredrickson and Prof. Hiroshi Watanabe, who have both stepped down as Associate Editors. The journal has benefitted tremendously from Glenn's keen insights, careful analysis, and steady hand.…”
mentioning
confidence: 99%
“…In particular, he developed a definitive understanding of the thermodynamics and hydrodynamics of DNA confinement in nanochannels for genome mapping technologies. More recent work has focused on the use of self-consistent field theory and coarse-grained molecular dynamics simulations of block polymer self-assembly and dynamics, including the origin of Frank–Kasper phases and micellar chain exchange …”
mentioning
confidence: 99%